Secondary Sarcopenia in Patients with Locomotor Disorders: Prevalence, Diagnosis and Medical Rehabilitation. A Review - Kirill D. Kuznetsov; Larisa A. Marchenkova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2024)
INTRODUCTION. The development of rehabilitation methods for patients with sarcopenia, a generalized age-associated loss of skeletal muscle mass and strength, is important, since sarcopenia leads to pronounced weakness, functional and motor disorders and an increased risk of death in the elderly. AIM. To analyze the prevalence, features of pathogenesis, diagnosis of secondary sarcopenia, including against the background of motor disorders due to stroke, as well as methods of treatment and medical rehabilitation of such patients. MAIN CONTENT. Among the secondary forms, sarcopenia is of the greatest clinical importance against the background of the consequences of acute cerebrovascular accident (ACA), due to muscular atrophy associated with paralysis and immobility, spasticity, inflammation and denervation of muscles, malnutrition and intestinal absorption of protein and vitamin D. Recent studies show that the prevalence of sarcopenia in stroke patients in emergency hospitals is 8.5-33.8 %, according to other data - more than 42 %. Muscle weakness after a stroke contributes to a decrease in physical functions and the development of disability, and sarcopenia leads to adverse outcomes 90 days after a stroke. According to the meta-analysis, which included 7 cohort studies with a total sample of 1,774 patients who underwent ACA, 27.1 % of them had sarcopenia. Moreover, the presence of sarcopenia negatively affected the clinical and functional outcomes of ACA, as well as the results of medical rehabilitation (odds ratio: 2.42, 95 % confidence interval: 1.76-3.33, p 0.001). CONCLUSION. Despite the prevalence and relevance of this pathology, rehabilitation programs for patients with sarcopenia against the background of the consequences of ACA have not been developed. Isolated foreign publications demonstrate the effectiveness of certain methods of physical therapy and electrical stimulation, but the evidence base for their effectiveness is low.